Transcriptome analysis of the 2,4-dichlorophenoxyacetic acid (2,4-D)-tolerant cotton chromosome substitution line CS-B15sh and its susceptible parental lines G. hirsutum L. cv. Texas Marker-1 and G. barbadense L. cv. Pima 379 - Perez, Loida M.; Mauleon, Ramil; Arick, Mark A.; Magbanua, Zenaida V.; Peterson, Daniel G.; Dean, Jeffrey F. D.; Tseng, Te Ming (Frontiers in Plant Science, 2022)
The cotton chromosome substitution line, CS-B15sh, exhibits 41% lower injury from 2,4-D when applied at the field recommended rate of 1.12 kg ae ha-1 (1x) than does Texas Marker 1 (TM-1). CS-B15sh was developed in the genetic background of G. hirsutum L. cv TM-1 and has chromosome introgression on the short arm of chromosome 15 from G. barbadense L. cv. Pima 379. In a previous experiment, we observed reduced translocation of [14C]2,4-D outside the treated leaf tissue in CS-B15sh, which contrasted with an increased translocation of the herbicide in the tissues above and below the treated leaf in TM-1. Our results indicate a potential 2,4-D tolerance mechanism in CS-B15sh involving altered movement of 2,4-D. Here, we used RNA sequencing (RNA-seq) to determine the differential expression of genes between 2,4-D-challenged and control plants of the tolerant (CS-B15sh) and susceptible lines (TM-1 and Pima 379). Several components of the 2,4-D/auxin response pathway – including ubiquitin E3 ligase, PB1|AUX/IAA, ARF transcription factors, and F box proteins of the SCFTIR1/AFB complex – were upregulated with at least 3-fold higher expression in TM-1 compared with CS-B15sh while both Pima 379 and TM-1 showed the same fold change expression for PB1|AUX/IAA mRNA. Some genes associated with herbicide metabolism, including flavin monooxygenase (Gohir.A01G174100) and FAD linked oxidase (Gohir.D06G002600), exhibited at least a 2-fold increase in CS-B15sh than in TM-1 (the gene was not expressed in Pima 379), suggesting a potential relationship between the gene’s expression and 2,4-D tolerance. It is interesting to note that glutathione S-transferase was differentially expressed in both CS-B15sh and Pima 379 but not in TM-1 while cytochrome P450 and other genes involved in the oxidation-reduction process were significantly expressed only in CS-B15sh in response to 2,4-D. Gene set enrichment analysis on the union DEGs of the three cotton genotypes revealed the depletion of transcripts involved in photosynthesis and enrichment of transcripts involved in ABA response and signaling.